PROFITABILITY DETERMINANTS MODEL: THEORETICAL AND METHODOLOGICAL ANALYSIS OF RESEARCH - Aprih Santoso; Teguh Ariefiantoro (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2019)
The purpose of this study was to analyze the effect of liquidity (CR) to profitability (ROA) through capital structure (DR) at companies listed on the Stock Exchange Year 2013-2017.The samples taken by purposive samplingof manufacturing companies the period 2013 - 2017.The test results and analysis of the data it can be concluded that liquidity (CR) directly and indirectly has no effect on profitability (ROA) through capital structure(DR) and showed no significant results.